Pengaruh Suasana Belajar Terhadap Keaktifan Belajar Mahasiswa MSDMA Angkatan 22 Di Kampus Politeknik STIA Lan Jakarta - Abdul Fahrevi Rajab; Dian Indriyani (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research aims to investigate the influence of the learning atmosphere on the learning activity of MSDMA Batch 22 students at the Stialan Polytechnic Campus, Jakarta. In the context of higher education, the learning atmosphere plays an important role in influencing the level of student engagement and learning success. Through this study, we explore the factors that influence students' active learning in the campus environment, with a focus on motivation, involvement, learning facilities, diversity of learning approaches, and collaboration between fellow students. The research method used was a survey with a questionnaire distributed to MSDMA Batch 22 students at the Stialan Polytechnic Campus, Jakarta. Data was collected and analyzed using descriptive statistical techniques and regression analysis to assess the relationship between the variables studied. The research results show that the learning atmosphere has a significant influence on the learning activity of MSDMA Batch 22 students on the campus. Motivation, involvement, learning facilities, diversity of learning approaches, and collaboration between students all have different contributions to active learning. These findings highlight the importance of creating a learning environment that supports and motivates students to be actively involved in the learning process. The practical implication of this research is that educational institutions need to pay attention to and improve the factors that influence the learning atmosphere on campus, such as providing adequate learning facilities, encouraging active student participation in learning, and paying attention to diversity in learning approaches. In this way, it is hoped that it can increase student learning activity and improve the quality of education at the Stialan Jakarta Polytechnic Campus